If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x-1)=7-x
We move all terms to the left:
5(x-1)-(7-x)=0
We add all the numbers together, and all the variables
5(x-1)-(-1x+7)=0
We multiply parentheses
5x-(-1x+7)-5=0
We get rid of parentheses
5x+1x-7-5=0
We add all the numbers together, and all the variables
6x-12=0
We move all terms containing x to the left, all other terms to the right
6x=12
x=12/6
x=2
| 2(c-15)=-10 | | 22-3y=-8 | | -9=−9=27+3y | | 6=2p+4 | | 14x=52/5 | | 2(5x+5)=-40+30 | | 9-3.2h=25 | | -9=27+3y27+3y | | 76=9y | | 18y+3=19 | | 9v−7=10v | | 4x+6=x-14 | | 3b=b | | 7-2f=9 | | z7+9=-14 | | 40+16x+12=180 | | 17x+13+5x-9=180 | | v+-9=1 | | 4x-32=2x+13 | | s-4=-3 | | k6+5=20 | | 4(x-3)=8x+4 | | g−74=86 | | 0.8(4-a)=-5.6a | | g−-74=86 | | 8d+7=31 | | -21.5+2.5r=8(3.5r+4) | | 10=-2f | | -2v-4=4 | | 2x−10=−3x | | 182=77-x | | 6h=-8+7h |